GOVERNMENT COMMUNICATION PATTERNS IN EFFORTS TO IMPROVE COMMUNITY WELFARE IN TUWUNG VILLAGE, BARRU DISTRICT, BARRU DISTRICT - Pratiwi, Dian; Sukmiah; Muliati Manda (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal